Accionar de enfermería en la prevención de complicaciones en el adulto con cirrosis hepática. - Palate Supe, Evelyn Ximena (2022)
Liver Cirrhosis is a serious disease caused by liver cells tissues deterioration and loss, whichis considered one of the main causes of morbidity and mortality in recent years. The most frequently worldwide etiologies of cirrhosis are, chronic infection by hepatitis B and C virus, chronic alcohol intake, hepatotoxic drugs and non-alcoholic fatty liver disease; it is known for being a silent disease also called compensated phase due to the absence of symptoms andthe other decompensated phase because it already presents complications. A documentary and systematic study was elaborated, with the objective of identifying the nursing actions associated with nursing diagnoses frequently used in the NANDA taxonomy (North American Nursing Diagnosis Association), NIC (Nursing Interventions Classification) and NOC (Nursing Outcomes Classification) applying a theoretical nursing model that contributes to nursing actions, by compiling information from several papers published in scientific databases: Scielo, Pubmed, Elsiever, ProQuest, Google Scholar, Clinical Practice Guides and university repositories; distributed within 2017 to 2022, of which 87 articles weretaken for the literature review. For the research results, first the coincidence of authors regarding the most frequent complications of liver cirrhosis was identified, then the clinical picture of the pathologies was analyzed, as well as their treatment, then nursing care was inquired and finally the authors' criteria were related to the NIC interventions. The main cirrhotic complications are: esophageal varices, ascites, hepatorenal syndrome, hepaticencephalopathy and malnutrition. The most common care: monitoring of vital signs, administration of analgesic and antibiotic medication, monitoring the state of consciousness,healthy and balanced diet, emotional support, patient and family education for discharge plancare.